The Flight of Icarus : European legal responses resulting from the financial crisis - Drossos, Yiannis (London : Bloomsbury Publishing, 2020)
"This book provides a detailed analysis of the institutional transformations brought about by the financial crisis, focusing on the institution-building course of Europe and the Constitution-bending course in several Member States. It discusses the seemingly contradictory interplay between national and European institutions and the law resulting from the crisis, arguing that the anti-crisis exceptionality constitutes the matrix of the new normality of the reformed European economic governance. The author carries out a critical analysis of the new economic governance and its case-law with regular reference to relevant political episodes, key economic figures and to the lax preceding modes and rules. The author also offers deep insights into the Greek adjustment programme and the crisis-related Greek and Portuguese constitutional case-law, presented in comparison with the German and French case-law. The book concludes with a critical overview of the profound mutations in the role of national Constitutions, instigated by the new European economic governance, and the emergence of a democratically deficient meta-constitutional mode of functioning of both the European institutions and national Constitutions"--
Conceptual flaw, original sin, and misapplications of the Maastricht Treaty -- The Greek memoranda -- Institutional creativity -- The two sides of the coin : constitutional reviews of the crisis legislation -- The Schmittian and the Madisonian moments of the crisis and the fate of the Constitution -- Gleichschaltung or a metaconstitutional Catallaxy.
Includes bibliographical references (pages 173-202) and index.
Compatible with accessibility standards for most Level A (Priority 1) and AA (Priority 2) success criteria of the Web Content Accessibility Guidelines (WCAG 2.0) developed by the Worldwide Web Consortium (W3C).
Keywords: Icarus -- (Greek mythological character); Treaty on European Union -- (1992 February 7); Monetary policy -- European Union countries; Debts, Public -- Law and legislation -- European Union countries; Finance, Public -- Law and legislation -- European Union countries; International and municipal law -- European Union countries; European Union countries -- Economic policy; Law; Constitutional and Administrative Law (Law); European Law (Law); Banking and Financial Law (Law)